ORGANIZATIONAL COMMITMENT, UNION COMMITMENT AND/OR CAREER COMMITMENT - Franck BIÉTRY; Patrice LAROCHE (Revue de Gestion des Ressources Humaines, 2011)
A number of studies in organizational behavior tend to examine the multi-dimensional nature of commitment. As the quality of the social dialogue is seen as an important issue for HR managers, it is interesting to question unionized employees behavior and especially the relationship between union commitment, organizational commitment and career commitment. Can unionized employees develop simultaneous commitments to their unions, their employing organizations and their career? To answer this question, we conduct an empirical analysis using a large survey in the private sector. The results indicate that unionized employees can be committed simultaneously to their union, their company and their career. However, this multidimensional nature of commitment is finally contingent upon specific professional categories and implies to be modest in terms of managerial practices.